Enzymatic and non-enzymatic functional attributes of plant microbiome. (June 2021) - Das, Joyati; Yadav, Sunil Kumar; Ghosh, Srayan; Tyagi, Kriti; Magotra, Ankita; Krishnan, Aiswarya; Jha, Gopaljee
Graphical abstract: Highlights: Microbiome assists in plant growth and resilience to environmental conditions. Restructuring of microbiome provides environmental adaptive capabilities to plants. An intricate molecular cross-talk regulates plant microbiome interactions. Microbiome is enriched in novel enzymes and natural products. Enzymatic and non-enzymatic functions of microbiome have industrial implications. Abstract : Microbiome plays an important role in plant growth and adaptation to various environmental conditions. The cross-talk between host plant and microbes (including microbe–microbe interactions) plays a crucial role in shaping the microbiome. Recent studies have highlighted that plant microbiome is enriched in genes encoding enzymes and natural products. Several novel antimicrobial compounds, bioactive natural products and lytic/degrading enzymes with industrial implications are being identified from the microbiome. Moreover, advancements in metagenomics and culture techniques are facilitating the development of synthetic microbial communities to promote sustainable agriculture. We discuss the recent advancements, opportunities and challenges in harnessing the full potential of plant microbiome.